Determinants of corn farmers to adapt to climate change impacts in Sagbayan, Bohol, Philippines - Centino, Zyra May H.; Vista, Arvin B. (Annals of Tropical Research, 2018)
The need to adapt to the negative impacts of climate change is urgent especially in the agriculture sector. However, there have been no published reports whether upland corn farmers are applying climate change adaptation strategies. This study sampled 91 upland corn farmers in Sagbayan, Bohol, Philippines to determine the factors affecting their decision to employ adaptations strategies. The adaptation strategies are those soil and water management and conservation techniques employed by farmers, which is modelled using binary logistic regression. The average age of the respondents was 56 years old. Respondents have been in corn production for an average period of 30 years. More than 50% of their annual household income comes from farming (PhP 25,393). Results showed that gender, farm income, total land used in farming and value of farm assets were the determinants of farmers’ use of adaptation strategies. Overall, corn farmers are knowledgeable of the impacts of climate change; however, employment of adaptation strategies is minimal. Hence, intervention should focus on programs that will increase probability of farmers employing adaptation strategies. Such programs may include farm-to-market roads to minimize post-harvest losses, setting of farmer field school and information drive.